Estilos de crianza y el desarrollo de competencias emocionales en los niños y niñas de Preparatoria. - Cisneros Quishpe, Katherine Margoth (2021)
The present research work was developed after the problem of inappropriate parenting styles of parents and how it affects the development of emotional competencies in their children, in such a way that the main objective was to look for alternatives that allow parents to choose an appropriate parenting style for a good development of emotional competencies of their children. The mixed approach was applied through interviews with the authorities, surveys of parents and an observation sheet for the high school students of the “Guangaje” Educational Unit in order to know the state of emotional competencies of the children and the parenting styles that parents are applying. After obtaining the necessary information, it was considered pertinent to develop a proposal framed in "Workshops for parents with activities to improve the parenting style and emotional development of children." Which consisted of 8 workshops. It was concluded, after the analysis of the pre-test and post-test of the observation sheet applied to high school students, that this proposal is applicable and that it caused a great impact on parents since an appropriate parenting style helps the child to know, develop and manage their emotions, so we will have happy and autonomous children, growing within the affective bond that is the family. Given that parents and children have responded favorably, it is recommended to include these activities in the family's life so that children can develop in a place of safety and love.